ANALISIS PEMILIHAN LOKASI TEMPAT PEMROSESAN AKHIR SAMPAH BERBASIS SISTEM INFORMASI GEOGRAFIS (SIG) DI KABUPATEN MINAHASA TENGGARA - Merry N. M. Kosakoy; Steenie E. Wallah; Herawaty Riogilang (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2022)
Southeast Minahasa Regency experiences an increase in population every year. This increase resulted in an increase in the volume and type of waste. The Final Processing Site (FPS) is the final stage of waste processing. Waste from collection or transportation and the rest of the results from recycling processing in an area or city is accommodated for management. For this reason, FPS must be prepared correctly and follow applicable standards so as not to pollute the surrounding environment and harm the community. The purposes of this study are 1) to determine the stages of selecting a landfill site according to applicable standards using a Geographic Information System (GIS); 2) to find out where the alternative location for the final waste processing site (FPS) is in Kab. Southeast Minahasa. The method used is descriptive quantitative. Based on the results of the research, the stages of choosing the FPS location based on SNI 03-3241-1994 and the Regulation of the Minister of Public Works of the Republic of Indonesia Number 03/PRT/M/2013 there are three stages, namely the Regional Stage, the Provisioning Stage, and the Determination Stage. The three stages were analyzed using GIS with Buffering and Overlay methods with a Binary quantitative approach. The location that became an alternative to FPS with the highest score of 311 was in Pusomaen District. The location is quite far from the existing FPS location; hence the selected FPS alternative can be input for the government for spatial planning in the Southeast Minahasa Regency area.